Reduction of Radiation Risk to Cardiologists and Patients during Coronary Angiography: Effect of Exposure Angulation and Composite Shields - Malekzadeh, Reza; Tarighatnia, Ali; Mehnati, Parinaz; Nader, Nader D. (Frontiers in biomedical technologies, 2024)
Purpose: This study aimed to design an improved form of a composite shield with different materials and shapes and simultaneously reduce the radiation dose to both the patient and operator. Materials and Methods: A female phantom study was performed with and without bismuth belt-shaped composite shields on the breast region at different beam projections used in coronary angiography. Dose measurements were conducted using GR-200 thermo-luminescence dosimeters, dose area product (DAP), and air kerma (AK) over regular and large breast locations, with and without using bismuth shields. An electronic personal dosimeter was used for operator dose assessment. Patients received doses between 2.27 mSv and 3.38 mSv, depending on the size and strength of beam projections. Results: The use of the developed shields caused a dose reduction of 18%–25% of sensitive breast tissue due to breast size and shield type. During coronary angiography, the mean values of DAP and AK were 2.02 (1.24-2.80) mGy.m2 and 314.1 (202.8-500) mGy, respectively. The highest recorded dose was at the LAO/CRA and LAO/CAU beam projections for both the patient and operator. After applying a belt shield, the operator's radiation dose was decreased by approximately 32%. We found a statistically significant correlation between the radiation dose received by the operator and the patient's breast radiation exposure dose (p<0.001, r2=0.93). Conclusion: The designed belt shield can be a potentially promising protective device for decreasing the radiation risk to the patient's breast and the operator during coronary angiography. However, further studies will be considered before the application of this shield in standard clinical practice.